The Effect of Enhanced External Counter Pulsation on Improving Quality of Life in Patient with 3 Vessels Disease Treated Medically Versus Percutaneous Coronary Intervention, 1 Year Follow Up - Ali Yahya Abdullah; Basim Abd Ali Saeed; Hassan Ali Essa Al mamuri; Ahmed Abdulzahra Jeyad Almurshidy (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background : Refractory angina usually refers to as (equal or more than 3 months in duration) stableischemic heart disease which cannot be regulated by a therapeutic treatment, surgical cardiac intervention,and where reversible cardiac ischemia has been stated to be the reason for the manifestation clinically.Aim:The efficacy of use enhanced external counter pulsation in treating refractory angina pectoris in those do PCIvs. medical alone and short-term outcome. PMethodology: 91 patients with refractory angina pectoris unrespond to treatment and/or intervention or unfit for intervention or surgery have been enrolled in this study,for all ECG, echocardiography study done to assess LV and valvular function, Doppler study for lower limbartery to assess if there is peripheral vascular disease, abdominal ultrasound done to exclude the presenceof aortic abdominal aneurysm, then if patient eligible for EECP inclusion criteria refer for EECP unit .Afterend of all session all patients assess improvement according to change in Canadian cardiovascular societygrading CCS pre and post EECP and on follow up 6 month and 1 year. Result: Over 12 month’s period of thestudy, 91 persons were assessed including 32(35%) women and 59 (65%) men. The age range was 45 yearsto 80 years with the mean age range 61 years (SD ± 8.2). Most patients treated with 30 session with 1 hourper session on average of 26 (SD ± 7) session with response rate at end of sessions 88.7% where responsemean improvement of symptom and according to (CCS) change per and post EECP.Conclusion: No befit from doing single vessel intervention in patient with 3 vessels disease in improvingresponse to EECP or improving echocardiographic parameter. EECP appear as safe effective therapy inselective patient with refractory angina not respond to medical and unfit for intervention or surgery. Responseto EECP in well selected patient persist for 1 year.